Pengembangan Modul Matematika Berbasis Etnomatematika Budaya Lokal Untuk Meningkatkan Literasi Numerasi Siswa SMP Negeri 1 Yogyakarta - Anwar, Ahmad; Ramadhani, Sulistyo (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to develop a mathematics module based on ethnomathematics rooted in local culture as an effort to improve students' numeracy literacy at SMP Negeri 1 Yogyakarta. The background of this research is based on the importance of linking mathematics learning with students’ cultural contexts to foster learning interest and a deeper understanding of concepts. The ethnomathematics approach used in the module development integrates local cultural values—such as batik patterns, traditional games, and regional architectural styles—into mathematics material taught at the junior high school level. The research method employed is Research and Development (R&D) using the 4D development model (Define, Design, Develop, Disseminate). The research subjects were eighth-grade students at SMP Negeri 1 Yogyakarta. Validation results from material and media experts indicated that the developed module is suitable for classroom use. A limited trial also showed an improvement in students’ numeracy literacy skills after using the module. Additionally, students responded positively to content that was connected to their own culture, which encouraged active participation in learning. These findings suggest that integrating ethnomathematics into mathematics instruction not only enhances conceptual understanding but also strengthens students' cultural identity. Therefore, this module can serve as an innovative alternative to improve the quality of mathematics learning in schools.